Agricultural Transformation and Local Resilience in Post Conflict Aceh: A Sustainable Livelihoods Analysis - A.R, M. Rizal Fazri; Emsa, Tasmiati; Harahap, Ali Azis Usman (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
Agriculture remains a central pillar of Aceh’s economy, yet the sector has not experienced substantial structural transformation despite post conflict recovery efforts. Persistent issues such as traditional cultivation practices, weak institutions, limited youth participation, and uneven access to production resources continue to constrain rural livelihoods. This study aims to analyze the dynamics of agricultural transformation, identify key factors shaping local economic resilience, and examine community based strategies that support sustainable agricultural development in a post conflict context. The research applied a qualitative descriptive approach grounded in the Sustainable Livelihood Framework. Fieldwork was conducted in Banda Aceh and Aceh Besar from May to September 2025 through in depth interviews, focus group discussions, and participatory observation involving twenty five purposively selected informants. Data were analyzed thematically using the interactive model of Miles, Huberman, and Saldaña, supported by triangulation and member checking to ensure validity. The findings show that transformation in Aceh remains uneven and is shaped more by administrative reforms than by changes in farming practices. Limited human capital, low youth engagement, and weak social cohesion slow the adoption of innovation. Institutional and financial constraints further restrict resilience, with farmers facing difficulties in accessing credit and formal support. At the same time, informal cooperation and customary leadership continue to play important roles in sustaining livelihoods. The study concludes that sustainable transformation is most effective when driven by community institutions that integrate human, social, and institutional capital. The research contributes to the literature by extending the Sustainable Livelihood Framework through the recognition of customary governance as a form of institutional capital in post conflict agrarian settings.